Soil mechanics - Craig, R. F. (Robert F.) (London ; New York : E & FN Spon, 1997)
As with previous editions, the aim of this text is to present the fundamental principles of soil mechanics and illustrate how they are applied in practical situations. This is reinforced by the inclusion of worked examples throughout the book
Basic Characteristics of Soils Seepage Effective Stress Shear Strength Stresses and Displacements Lateral Earth Pressure Consolidation Theory Bearing Capacity Stability of Slopes
Includes bibliographical references and index
Keywords: Soil mechanics